2015
DOI: 10.3322/caac.21259
|View full text |Cite
|
Sign up to set email alerts
|

Anal cancer: Current standards in care and recent changes in practice

Abstract: https://www.wileyhealthlearning.com/acs.aspx The management of squamous cell carcinomas of the anal canal has evolved from surgery as first‐line treatment to curative chemoradiation, with surgery reserved for salvage. Significant progress has been made in understanding how to most effectively deliver chemotherapy and reduce toxicity through advancements in radiation delivery. The purpose of this article is to review the multimodality approach to the diagnosis and management of anal cancer based on a review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 180 publications
(353 reference statements)
0
54
0
4
Order By: Relevance
“…[2] Knowing that anal cancer is caused by HPV in a similar way to cervical disease is helpful, but there is a lack of data guiding anal cancer screening recommendations. Most experts recommend anal screening for HIV+ men and women as well as men who have sex with men [3], and the American Cancer Society suggests that those at increased risk of anal intraepithelial neoplasia (AIN) may benefit from screening, including women who have had cervical or vulvar cancer [4]. A recent study by Slama, et al examined 172 high-risk women with cervical intraepithelial neoplasia 2 or greater (CIN2+) compared to 100 women with non-neoplastic gynecologic disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Knowing that anal cancer is caused by HPV in a similar way to cervical disease is helpful, but there is a lack of data guiding anal cancer screening recommendations. Most experts recommend anal screening for HIV+ men and women as well as men who have sex with men [3], and the American Cancer Society suggests that those at increased risk of anal intraepithelial neoplasia (AIN) may benefit from screening, including women who have had cervical or vulvar cancer [4]. A recent study by Slama, et al examined 172 high-risk women with cervical intraepithelial neoplasia 2 or greater (CIN2+) compared to 100 women with non-neoplastic gynecologic disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hannes et al [27] confirmed a good 5-year survival rate of 86% in patients who underwent salvage surgery, with a longer survival of T0/T1 stage, than compared to patients presenting with T2/T3/T4 tumors. A recent review of literature confirmed the good survival rate of patients with recurrence disease after CRT, which showed the negative resection margin (R0) as the most significant prognostic factor [28] . In our study, the overall survival rates at 1, 3, and 5 years were 75, 60, and 37.4%, with disease-free survival rates of 67, 53, and 35%, respectively.…”
Section: Oncological Results Of Surgical Salvage Surgerymentioning
confidence: 91%
“…The primary aim of treatment is to achieve cure with locoregional control and preservation of anal function [3,4] . Chemoradiation remains the standard of care leading to complete tumor regression in 80-90% of patients [3,14] .…”
Section: Discussionmentioning
confidence: 99%
“…SCCA is underrecognized due to the perceived rarity of the disease and because the inspection of the anal and perianal region is frequently neglected [14] . The diagnosis is delayed, not only due to medical misdiagnosis but also because in the beginning of symptoms patients defer medical attention and refuse observation (patient 3).…”
Section: Discussionmentioning
confidence: 99%